2019
DOI: 10.1096/fasebj.2019.33.1_supplement.453.13
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ultrasound‐Guided Localization of the Peripatellar Plexus for Knee Pain Management

Abstract: IntroductionPain associated with arthritis of the knee and its ultimate treatment, total knee arthroplasty, can be considerable and has historically been addressed with a variety of treatment modalities including an emphasis on opioid usage for severe pain. While opioids provide effective pain relief, they have many unwanted side effects including nausea, vomiting, constipation, urinary retention, mental status changes, and respiratory depression. Alternatively, patients experiencing knee pain have benefited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Current studies of PP focusing on either anatomy or ultrasound have examined only some of the four nerves of PP and have fallen short in terms of details, impeding the development and clinical application of PP block. A cadaver study under ultrasound confirmed the feasibility of block for several PP branches, but this study demonstrated a poor success rate with IPBSN block and did not provide details on identifying among the MFCN, IFCN I and IFCN II under ultrasound [25]. Another cadaveric study under ultrasound identified only the MFCN and one branch of the IFCN, with no detailed identification of the PP branches [26].…”
Section: Discussionmentioning
confidence: 83%
“…Current studies of PP focusing on either anatomy or ultrasound have examined only some of the four nerves of PP and have fallen short in terms of details, impeding the development and clinical application of PP block. A cadaver study under ultrasound confirmed the feasibility of block for several PP branches, but this study demonstrated a poor success rate with IPBSN block and did not provide details on identifying among the MFCN, IFCN I and IFCN II under ultrasound [25]. Another cadaveric study under ultrasound identified only the MFCN and one branch of the IFCN, with no detailed identification of the PP branches [26].…”
Section: Discussionmentioning
confidence: 83%